1994
DOI: 10.2355/isijinternational.34.265
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Calcium-Oxygen Equilibrium in Liquid Iron.

Abstract: The first-order (ega) and the second-order ( Interaction Parameters betweenCalcium and Oxygen 2.1. Reciprocal and Conversion RelationshipsThe following reciprocal relationships among interaction parameters were derived by Lupis and Elliott,i6) p~,i+8J!=2p;+8:where 8~a nd +10gKc* """--"""""""""""""""-""',. The values for e~l7) and ac*018) used in this study are summarized in Table I and Fig. l

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 0 publications
2
50
0
Order By: Relevance
“…Several authors 13,14,[19][20][21][22] have attempted to model the Ca deoxidation curve using the classical Wagner formalism without considering the formation of associates. Very large negative temperature-dependent first-and second-order interaction parameters e Ca O , r Ca O , r Ca Ca,O were required.…”
Section: Associate Modelmentioning
confidence: 99%
“…Several authors 13,14,[19][20][21][22] have attempted to model the Ca deoxidation curve using the classical Wagner formalism without considering the formation of associates. Very large negative temperature-dependent first-and second-order interaction parameters e Ca O , r Ca O , r Ca Ca,O were required.…”
Section: Associate Modelmentioning
confidence: 99%
“…The complex deoxidation of liquid iron with silicon-aluminum was studied by Fujisawa et al, 2) but there is no report on the complex deoxidation of iron-high chromium alloys with silicon-aluminum. In metallurgical research of several decades, many studies have been reported on the thermodynamics of iron-chromium-oxygen [3][4][5][6] and ironaluminum-oxygen 3,[7][8][9] systems. Recently, one of present authors 10,11) has published assessment of thermodynamic values on above two systems in detail.…”
Section: Introductionmentioning
confidence: 99%
“…(5) to (8) are given in the previous articles. 7,9,10) It is assumed as a first approximation that the values of interaction coefficients between Ca and O depend on the Ca and O contents and are obtained by using Eqs. (5) to (8).…”
Section: Resultsmentioning
confidence: 99%